Parenting and stress: A study with Spanish and Portuguese at-risk families - Perez-Padilla, Javier (2019)
This study analyzed parenting stress, parental sense of competence, and stressful life events in families at psychosocial risk in Western Andalusia (Spain) and the Algarve (Portugal). Differences and similarities between families from both countries on these dimensions were explored, as well as the influence of country of origin in determining risk profiles for this population. Although both groups shared some sociodemographic characteristics, differences were found on all studied dimensions, with Portuguese mothers showing higher levels of parenting stress, sense of competence, and accumulation of stressful life events. Results suggest that higher risk families tend to share psychosocial characteristics, regardless of their country of origin.